Drivers of smart speakers' advertising acceptance - Ribeiro, Carolina Fiuza (2021)
The growing impact of technology on marketing communications is inevitable. That is why brands need to achieve the vision of these new technologies, which are becoming the new channels of communication and purchasing, to get closer to the consumer. Artificial Intelligence and, consequently, smart speakers are becoming one of the major trends in marketing, bringing benefits not only for brands but also for consumers. Thus, this study explores what factors may impact the acceptance of receiving advertising through these devices. This study's objective focuses on 329 Portuguese consumers' responses and uses a partial least square structural equation modelling to conduct an empirical study. The results indicate that the channel’s acceptance has a significant impact on consumers' acceptance of advertising and the hedonic motivations. However, it demonstrates that the perceived value and trust of advertising do not significantly impact its acceptance. The study suggests that smart speakers should benefit their users and have added functions that allow interaction with what is being advertised. Besides, the content that brands want to advertise should be relevant and contain information related to users' interests to generate positive feelings towards the ad, leading to a higher predisposition to accept advertising.